Do Not Forget Nephrotic Syndrome as a Cause of Increased Requirement of Levothyroxine Replacement Therapy - Benvenga, Salvatore (Eur Thyroid J, 2015)
Nephrotic syndrome increases L-thyroxine requirements because of urinary loss of free and protein-bound thyroid hormones. We report 2 hypothyroid patients referred to us because of high serum TSH, even though the L-thyroxine daily dose was maintained at appropriate levels or was increased. The cause of nephrotic syndrome was multiple myeloma in one patient and diabetic glomerulosclerosis in the other patient. As part of the periodic controls for diabetes, urinalysis was requested only in the second patient so that proteinuria could be detected. However, as in the first patient, facial puffiness and body weight increase were initially attributed to hypothyroidism, which was poorly compensated by L-thyroxine therapy. In the first patient, the pitting nature of the pedal edema was missed at the initial examination. An endocrinologist consulted over the phone by the practitioner hypothesized some causes of intestinal malabsorption of L-thyroxine. This diagnosis would have been accepted had the patient continued taking a known sequestrant of L-thyroxine, i.e. calcium carbonate. The diagnostic workup of patients with increasing requirements of L-thyroxine replacement therapy should not be concentrated on the digestive system alone. Careful history taking and physical examination need to be thorough. Endocrinologists should not forget nephrotic syndrome that, in turn, can be secondary to serious diseases.